1, 8‐Naphthyridinecarbaldehydes and Their Methyl‐Substituted Precursors: Synthesis, Molecular Structures, Supramolecular Motifs and Trapped Water Clusters. Issue 40 (27th October 2017) - Rosin, Robert; Seichter, Wilhelm; Schwarzer, Anke; Mazik, Monika
Abstract : 1, 8‐Naphthyridinecarbaldehydes bearing chlorine, pyrrolidinyl, piperidinyl or morpholinyl groups, were synthesised by oxidation of their methyl‐substituted precursors. The prepared carbaldehydes represent valuable starting materials for the construction of systems that are useful for supramolecular and medicinal chemistry. Single‐crystal X‐ray diffraction studies of four carbaldehydes and six methyl derivatives provided interesting information about the supramolecular motifs in the crystal structures of solvent‐free and solvated naphthyridines. The formation of interesting water clusters, for example, T4(2) water tape, was observed in the case of 7‐methyl‐2‐(piperidin‐1‐yl)‐1, 8‐naphthyridine as well as in the crystal structure of a by‐product 7‐(morpholin‐1‐yl)‐1, 8‐naphthyridine‐2‐carboxylic acid. Knowledge of the detailed structural properties of water clusters is of great research interest to a broad range of scientific disciplines. Abstract : Interesting supramolecular motifs and trapped water clusters have been recognised in the crystal structures of solvent‐free and solvated 1, 8‐naphthyridine derivatives.